Post a New Question

trig

posted by .

how do you start this equation i've been tryng it for 20min.

sec^6x(secxtanx)-sec^4x(secxtanx)=sec^5xtan^3x

ec^6x(secxtanx)-sec^4x(secxtanx)=sec^5xtan^3x


Factor out a sec^5 tan and divide thru. Left is

sec^2 x = Tan^2 x

Then this should reduce to
sin^2 x = cos^4 x
take the square root of each side
sin x= cos^2 x
change the cos squared to 1-sin^2
sin^2 x + sin x -1=0
Now you have a quadratic, use the quadratic equation.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question